2005
DOI: 10.1007/s00228-005-0892-y
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with angiotensin converting enzyme inhibitors, angiotensin-II-antagonists and beta-blockers in an unselected group of patients with chronic heart failure

Abstract: CHF was not optimally diagnosed in this cohort of patients. Correct diagnosing seems to be associated with more adequate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 19 publications
2
6
2
Order By: Relevance
“…All patients with heart failure will not be suitable for beta-blocker therapy but other studies found that 70-80% of unselected patients with heart failure are suitable for, and tolerate, beta-blocker therapy. 16,27,28 Compared with this, the present study's treatment rate with recommended beta-blockers of 24.7% is low and suggests the potential for further improvements in prescribing. If there is potential for a further 45% of patients to be treated with recommended beta-blockers, extrapolating the present findings to the whole of the UK, this would suggest up to 155 000 additional patients aged over 50 years could be treated.…”
Section: Implications For Clinical Practice and Future Researchcontrasting
confidence: 56%
See 2 more Smart Citations
“…All patients with heart failure will not be suitable for beta-blocker therapy but other studies found that 70-80% of unselected patients with heart failure are suitable for, and tolerate, beta-blocker therapy. 16,27,28 Compared with this, the present study's treatment rate with recommended beta-blockers of 24.7% is low and suggests the potential for further improvements in prescribing. If there is potential for a further 45% of patients to be treated with recommended beta-blockers, extrapolating the present findings to the whole of the UK, this would suggest up to 155 000 additional patients aged over 50 years could be treated.…”
Section: Implications For Clinical Practice and Future Researchcontrasting
confidence: 56%
“…The majority have studied hospital discharge or outpatient populations or were conducted outside the UK. [11][12][13][14][15][16] These studies have generally reported higher utilisation of beta-blockers. The EuroHeart Failure study, a survey of hospital discharges across 24 European countries, reported 36.9% utilisation in 2000-2001, with a lower proportion in the UK.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Studies in primary care show that a higher accessibility to a GP reduces the number of hospitalizations (96). Studies have shown that there is limited use in the PHC of medication recommended for HF, and when it is used, it is in in sub-optimal dosages (7,97).…”
Section: Heart Failure In Primary Healthcarementioning
confidence: 99%
“…When HF is based on clinical criteria, basically 50% of the patients will have an incorrect diagnosis (4,19,25,64). In comparison with other studies which are population-or PHC-based, echocardiography was applied in 8-30% of patients with the diagnosis of HF in the PHC (6,7,97). Consequently, there is a substantial risk that the diagnosis is incorrect and that patient will receive inappropriate treatment.…”
Section: Diagnostic Considerations Of Heart Failure In Primary Healthmentioning
confidence: 99%